Discontinuation strategies and long-term outcome of antidepressant medications - Bakhiader, Mohammad A.; Alsultan, Ibrahim; Alelowi, Abdulrahman; Aloufi, Mohammed; Almatrafi, Saleh; Aljohani, Fahad; Almuzaini, Tariq; Shalaby, Hasan; Abuhawi, Zobaidah; Nassif, Reyam; Showaihi, Shadi (International Journal Of Community Medicine And Public Health, 2023)
In terms of the treatment of depression, it is proven by many research that antidepressant drug has a significant impact on the treatment of depression patients. They can make them feel better and cope with their challenges. However, discontinuing these medications can be challenging due to concerns such as relapse, withdrawal symptoms, recurrence, and patient preferences. In this paper, we conducted a review of research on strategies for stopping antidepressants. Explored their long-term effects. By analyzing randomized controlled trials, cohort studies, systematic reviews, and meta-analyses, we gained insights into discontinuation methods and the extended impact of antidepressant use. Findings from quality evidence suggest that abruptly stopping antidepressants increases the risk of relapse or recurrence compared to reducing dosage or continuing with medication. Similarly, reducing dosage gradually helps in decreasing the risk and severity of withdrawal symptoms when compared to discontinuation or continued use without tapering off. Furthermore, psychological interventions like therapy or mindfulness-based cognitive therapy are identified as a best protocol for preventing relapse or recurrence after discontinuing antidepressants. These interventions are found to be particularly effective for patients experiencing symptoms or having risk factors. Additionally, although there is evidence regarding the long-term outcomes of using antidepressants beyond two years, some studies suggest that additional interventions such as patient education, shared decision-making processes monitoring progress, and providing feedback can assist in supporting successful discontinuation by improving adherence and patient satisfaction. In summary, stopping antidepressant medication is a process that necessitates assessment.